MENILIK AKUNTABILITAS AKUNTANSI DARI BUDAYA ISLAM - Daiyinta C.P Handoko; Syamsul Huda (Tirtayasa Ekonomika, 2018)
The relationship between Islam and accounting is that Islamic law, sharia, claims to govern all aspects of life, ethics, and social affairs. Every action taken must be in accordance with Islamic law and principles. Ethical principles define what is right, fair, corporate responsibility, and community priorities. Based on the ethical principles in Islam, accounting requires fairness and honesty in corporate responsibility, which refers to accountability, especially in non-profit companies or organizations.This research used a qualitative approach based on literature study to obtain a broad overview of accountability in Islamic culture. The result of this research is that accountability in Islam is an obligation that must be carried out as a form of accountability to interested parties or the wider community. This is in accordance with one of the main objectives of Islamic accounting, namely to provide information that frees those involved in the company from their accountability to the community.Keywords : Acountability Accounting, Islamic Culture